Architecture of rehabilitation facilities for people with visual impairments - Rybka, Adam; Szybka, Katarzyna (Видавництво Львівської політехніки, 2013)
There is a need to create common and consistent rules that would allow understanding disability as a phenomenon of the system. There are many different definitions of disability. The effects it entails visual dysfunction depends on several factors. The paper presents examples of rehabilitation and educational institutions for the visually impaired in Poland and abroad. The aim of the project was to develop th e concept of software – adaptive spatial resort for those who are completely blind or visually impaired is defined, which is used primarily for adaptation and educational purposes as well as therapeutic and convalescent. Multisensory space combines elements of architecture, art and media. The essence of architectural design and rehabilitation facilities are functional, simp le and intuitive to use, with an emphasis on open spaces and objects in such a way that their function was understandable for every user, regardless of experience or an advanced degree of dysfunction. Існує необхідність створення єдиних і послідовних правил, які дозволять зрозуміти інвалідність як системне явище. Є багато різних визначень інвалідності. Ефекти, які повязані з порушенням зору, залежить від кількох факторів. У статті наведено приклади реабілітаційних закладів для інвалідів в Польщі та за кордоном. Мета проекту полягала у створенні концепції – адаптивного просторового центру для повністю сліпих та слабозорих, яка використовується в основному для цілей адаптації і навчання, а також лікувальння та одужування. Мультисенсорний простір поєднує в собі елементи архітектури, мистецтва і засобів масової інформації. Суть проекту полягає у архітектурній функціональності об'єктів, простоті і інтуїтивно зрозумілому у використанні, з акцентом на дизайн простору і об'єктів таким чином, щоб їх функція була зрозуміла для будь-якого користувача, незалежно від досвіду.
Keywords: architecture; design; rehabilitation facilities; people with visual impairments; архітектура; проектування; реабілітаційні центри; люди з порушенням зору